2020
DOI: 10.3390/educsci11010008
|View full text |Cite
|
Sign up to set email alerts
|

Use of Augmented and Virtual Reality in Remote Higher Education: A Systematic Umbrella Review

Abstract: In this systematic umbrella review we aggregate the current knowledge of how virtual and augmented reality technologies are applicable to and impact remote learning in higher education; specifically, how they impact such learning outcomes as performance and engagement in all stages of higher education from course preparation to student evaluation and grading. This review was done as part of a state wide research effort of Latvia, to mitigate the impact of COVID-19 and specifically to provide a framework for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 53 publications
0
28
0
2
Order By: Relevance
“…A possible solution to overcome such a crucial limitation may arise from the use of easily accessible technological solutions that could allow students to collect, straight from their homes, movement-related data that can be integrated into the virtual learning environment and used by the teacher to assess the acquisition of specific skills [31]. Along those lines, a very promising perspective is that provided by the use of augmented reality for immersive learning of hands-on skills [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…A possible solution to overcome such a crucial limitation may arise from the use of easily accessible technological solutions that could allow students to collect, straight from their homes, movement-related data that can be integrated into the virtual learning environment and used by the teacher to assess the acquisition of specific skills [31]. Along those lines, a very promising perspective is that provided by the use of augmented reality for immersive learning of hands-on skills [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The digitalization and gamification of the educational process was adopted to cope with the new remote regime introduced due to the pandemic. The digital regulation, and game as a specific form of activity, however, influence the re-organization of life at work and for learning [70,71]. The lack of responsibility and the position of "things" [72] or "puppets" [73] has a deep impact on the behavior of all participants in learning.…”
Section: Discussionmentioning
confidence: 99%
“…It has been ascertained that with VR techniques students can have a knowledge retention rate of 75% compared to 10% with reading and 5% from lectures [25]. A recent systematic review [26] on the impact of VR on students' performance has identified 24 relevant studies, out of which reported a positive impact of VR on performance, whilst seven revealed a negative one, and six registered no significant impact. Moreover, VR techniques can help in the acquisition of procedural and declarative knowledge as well as the development of skills, such as problem solving, communication, and collaboration [25].…”
Section: Virtual Realitymentioning
confidence: 99%